HUBUNGAN PEMANFAATAN MEDIA PEMBELAJARAN PAI DENGAN MOTIVASI BELAJAR SISWA DI SMA N UNGGUL DHARMASRAYA KECAMATAN KOTO BARU KABUPATEN DHARMASRAYA - Fitria Suci Wulandari (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2021)
This research is constrained by students with experiencing the lack of student learning motivation caused by the use of learning media by the PAI teacher. Thus the students tend to lack the motivation to learn. Many students are less interested in the media used by teachers, there are even some students who do not understand the material that the teacher delivered, there are also unpregive, sleepy, boredoms at the time of following the PAI learning. The purpose of this study is to know if there is a relationship between the utilization of the PAI media with student learning motivation and to know how much the media endicule relationship is with student motivation at SMA N Unggul Dharmasraya. This research is a correlational quantitative type study. While the data used is primary data obtained by questionnaire using a kind of scale likes spread to 28 high school students Unggul Dharmasraya. Data analysis techniques in research are descriptive statistical analysis, normality test, simple linear regression test, product moment correlation test. The result of hypothesis test has a variable relationship of the media equivalent of media equivalent with student learning motivation. Thus it is stated that Ha accepted Ho rejected. Indicates that the proposion of the variable relationship of the media equivalent of media studies with student learning motivation is equal to 0.336 or 33.6%, while the remaining 66.3% is influenced by other variables that are not in the research that the authors do.